Waterbirth: current knowledge and medico-legal issues - Vidiri, Annalisa; Zaami, Simona; Straface, Gianluca; Gullo, Giuseppe; Turrini, Irene; Matarrese, Daniela; Signore, Fabrizio; Cavaliere, Anna Franca; Perelli, Federica; Marchi, Laura (Acta Biomedica Atenei Parmensis, 2022)
Water immersion during labour and birth has become increasingly popular and widespread in many countries, in particular in midwifery-led care settings. Nevertheless, there is a dearth of quality data about waterbirth, with currently available findings mostly arising from observational studies and case series. The lack of high-quality evidence and the controversial results reported by different studies determined a “behavioral gap” without clearly objective, consistent indications allowing for a sound and evidence-based decision making process. Although water immersion in the first stage of labour is generally considered a safe and cost-effective method of pain management for women in labor, concerns still linger as to the safety of immersion during the second stage of labor and delivery, particularly in terms of neonatal risks and medico-legal implications.